Usability Evaluation of a Virtual Reality Simulation System for Earthquake Preparedness Using the System Usability Scale (SUS) Method - Romeo Putra Dirama; Tranggono Tranggono; Rizqi Novita Sari (Newinera Publisher, 2026)
This study aims to evaluate the usability level of the Virtual Reality (VR) simulation system for earthquake preparedness training at the Environmental Agency of East Java Province using the System Usability Scale (SUS) method. The testing was conducted with nine respondents who performed two task scenarios in the simulation and subsequently completed the SUS questionnaire. The analysis covered three main aspects of usability: effectiveness, efficiency, and user satisfaction. The results showed an effectiveness level of 100% (“Highly Effective” category), an average efficiency of 0.01758 goals/second (“Very Fast” category), and an average SUS score of 73.88, which falls into the “Acceptable” category with an adjective rating of “Good.” These findings demonstrate that the VR simulation has strategic potential as an effective and efficient interactive training medium for improving the understanding of earthquake evacuation procedures. Nevertheless, improvements are needed in interface consistency and in reducing the initial learning curve to optimize the user experience.